1997
DOI: 10.1042/bj3260625
|View full text |Cite
|
Sign up to set email alerts
|

Comparative anatomy of the aldo–keto reductase superfamily

Abstract: The aldo-keto reductases metabolize a wide range of substrates and are potential drug targets. This protein superfamily includes aldose reductases, aldehyde reductases, hydroxysteroid dehydrogenases and dihydrodiol dehydrogenases. By combining multiple sequence alignments with known three-dimensional structures and the results of site-directed mutagenesis studies, we have developed a structure/function analysis of this superfamily. Our studies suggest that the (alpha/beta)8-barrel fold provides a common scaffo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
595
0
17

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 576 publications
(616 citation statements)
references
References 99 publications
4
595
0
17
Order By: Relevance
“…Before the initiation of parturition, the progesterone level decreases markedly due to 20a-HSD induction, which is a cytosolic enzyme that converts progesterone to the inactive form 20a-hydroxyprogesterone (20a-OHP), in the corpus luteum of rodents (Wiest 1959;Batra et al 1976). Recently, cDNAs encoding rabbit [AKR 1C5] (Lacy et al 1993) and rat [AKR 1C8] (Mao et al 1994;Miura et al 1994) 20a-HSDs were isolated, and 20a-HSD is classi®ed as an aldo-keto reductase (AKR) (1997b; Jez et al 1997a). The AKR superfamily consists of monomeric NAD(P)(H)-dependent oxido-reductases with a broad speci®city of substrates: endogenous substrates, such as steroid hormones and prostaglandins (PGs); and xenobiotics, such as drugs and carcinogens.…”
Section: Introductionmentioning
confidence: 99%
“…Before the initiation of parturition, the progesterone level decreases markedly due to 20a-HSD induction, which is a cytosolic enzyme that converts progesterone to the inactive form 20a-hydroxyprogesterone (20a-OHP), in the corpus luteum of rodents (Wiest 1959;Batra et al 1976). Recently, cDNAs encoding rabbit [AKR 1C5] (Lacy et al 1993) and rat [AKR 1C8] (Mao et al 1994;Miura et al 1994) 20a-HSDs were isolated, and 20a-HSD is classi®ed as an aldo-keto reductase (AKR) (1997b; Jez et al 1997a). The AKR superfamily consists of monomeric NAD(P)(H)-dependent oxido-reductases with a broad speci®city of substrates: endogenous substrates, such as steroid hormones and prostaglandins (PGs); and xenobiotics, such as drugs and carcinogens.…”
Section: Introductionmentioning
confidence: 99%
“…The sequences of the five dimeric DDs did not show significant similarity to the aldo-keto reductase family proteins including monomeric DDs [11], but Asp-49, Tyr-55 and Lys-91 of the dimeric enzymes (other than rabbit DD) almost correspond to the important residues in the catalysis of the aldo-keto reductase family enzymes [11]. The Tyr residue has been demonstrated by site-directed mutation into Phe to be the catalytic residue of the aldo-keto reductases [43,44].…”
Section: Alignment Of Dimeric Dds With Other Proteinsmentioning
confidence: 91%
“…The enzyme exists in multiple forms in mammalian tissues. Most of the enzymes purified from various mammalian tissues are monomeric and have been shown to be identical with 3α-, 17β-and 20α-hydroxysteroid dehydrogenases, aldehyde reductase and\or aldose reductase [5][6][7][8][9][10], which are members of the aldo-keto reductase superfamily [11]. In addition to the monomeric enzymes, dimeric DDs composed of 39 kDa subunits have been isolated from rabbit lens [10], monkey kidney [12,13], pig tissues [14] and dog liver [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the multiple sequence alignment analysis of these polypeptides ( Fig. 1), it was observed that the selected proteins possess a classic Rossmann-fold structure containing the catalytic tetrad D-X 4 -Y-X n -K-X n -H (Jez et al 1997). In addition, the signature sequences (PROSITE Accession No.…”
Section: Discovery Of Potential Akrsmentioning
confidence: 99%